Association between sociodemographic, anthropometric variables, life habits and postural balance of pregnant women: a cross-sectional study - Sousa, Vanessa Patrícia Soares de; Cury, Alethéa; Sousa, Sara Estéfani Soares de; Ribeiro, Silvia Oliveira; Viana, Elizabel de Souza Ramalho (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Researchers have sought to evaluate the relationship between sociodemographic characteristics and life habits in maintaining the postural balance of specific populations. However, studies based on analyzing in detail the influence of these factors on this body function in pregnant women are scarce. Objective: To analyze the association between sociodemographic, obstetric, anthropometric and lifestyle characteristics and changes in postural balance in pregnant women. Method: Cross-sectional study carried out from February 2012 to March 2015 at the Federal University of Rio Grande do Norte (UFRN). The sample consisted of 263 pregnant women. Balance Master System® (NeuroCom, Clackamas, USA) was used for balance evaluation. The bivariate analysis was performed by applying the chi-square test (x2 ). Results: The results suggest that the absence of alterations in the variables related to static postural balance is associated with higher levels of education, higher income and age over 29 years (x2 = 4.73, P = 0.03). In addition, during the evaluation of the dynamic balance, it was verified that the absence of abnormalities is related to income higher than 4 minimum wages (x2 = 3.98, P = 0.04), while changes in lateral displacement were associated with lower body weight (up to 68 kg) (x2 = 12.2, P = 0.03). Conclusion: There is an association between sociodemographic characteristics, life habits and changes in the postural balance of pregnant women.